Consideraciones sobre las tensiones en la intermediación política del movimiento cocalero en el Perú - Zevallos, Nicolás (2013)
In Peru, the coca growers’ movement emerged as a response to the State stance against the proliferation of illicit cultivation of coca leaf. To defend this product, this social movement has appealed mainly to three kinds of actors: pressure groups, political parties and insurgent groups. This article points that, in the exercise of this intermediation, these three actors deploy contradictory discourses and practices, according to the political arenas in which the movement requires navigate to defend the cultivation of the coca leaf.